Autonomous synthesis system integrating theoretical, informatics, and experimental approaches for large-magnetic-anisotropy materials. Issue 1 (31st December 2022) - Furuya, Daigo; Miyashita, Takuya; Miura, Yoshio; Iwasaki, Yuma; Kotsugi, Masato
ABSTRACT: We developed an autonomous and efficient system for synthesising ferromagnetic materials with large magnetocrystalline anisotropy by integrating theoretical, informatics, and experimental approaches. By combining the first-principles calculation of the magnetic anisotropy with Bayesian optimisation, we virtually screened candidate materials, comprising four elements and four-layer periods, from various magnetic multilayers. We employed the expected improvement as the acquisition function and Matern52 as the kernel function, to develop a robust machine learning model. We fabricated the top three predicted magnetic materials under laboratory conditions by monoatomic layer deposition and evaluated their magnetic anisotropy using a superconducting quantum interference device (SQUID). Ultimately, we demonstrated that [Fe/Co/Fe/Ni]13 is a novel ferromagnetic material whose magnetic anisotropy exceeds that of L 10 -FeNi- and L 10 -FeCo-type alloys. Furthermore, the origin of the perpendicular magnetic anisotropy was derived from the spin-conserving as well as the spin-flip terms. We determined that Bayesian optimisation offers promising configurability features in terms of the electronic structure that extend beyond the empirical knowledge and human intuition. Graphical abstract: uf0001